Soil quality after eight years under high tunnels - Knewtson, Sharon J. B.; Kirkham, Mary B.; Janke, Rhonda R.; Murray, Leigh W.; Carey, Edward E. (My University, 2013)
The sustainability of soil quality under high tunnels will influence management of high tunnels currently in use and grower decisions regarding design and management of new high tunnels to be constructed. Soil quality was quantified using measures of soil pH, salinity, total carbon, and particulate organic matter (POM) carbon in a silt loam soil that had been in vegetable production under high tunnels at the research station in Olathe, KS, for eight years. Soil under high tunnels was compared with that in adjacent fields in both a conventional and an organic management system. The eight-year presence of high tunnels under the conventional management system resulted in increased soil pH and salinity but did not affect soil carbon. In the organic management system, high tunnels did not affect soil pH, increased soil salinity, and influenced soil carbon (C) pools with an increase in POM carbon. The increases in soil salinity were not enough to be detrimental to crops. These results indicate that soil quality was not adversely affected by eight years under stationary high tunnels managed with conventionally or organically produced vegetable crops.
Keywords: Hoophouse; Particulate organic matter carbon (POM C); Salinity